Un voyage à hauts risques : l’exil clandestin des protestants vers Genève après la révocation de l’édit de Nantes - Pierre Coulet (Diasporas: Circulations, Migrations, Histoire)
In this paper, through testimonies of refugees, we describe some routes clandestinely used by protestants after the revocation of the edict of Nantes (1685), between the south-east of France and Geneva. Among the common features emanating from these accounts, we can note the constant fear of being identified as a fugitive and betrayed, the vulnerability and dependence on guides whose fairness remains uncertain, the importance of money to pay for any kind of help or complicity, not omitting the hardships of such a route. In this way, comparisons with situations met nowadays are possible.